Attitude and Behavior Towards Covid-19 Control Among High School Students in Surabaya and Sidoarjo, Indonesia - Muhammad Nuh Ihsan; Ahila Meliana; Nurina Hasanatuludhhiyah; Visuddho Visuddho; Abdul Khairul Rizki Purba; Annete D'Arqom (Journal of Community Medicine and Public Health Research, 2023)
Morbidity and mortality due to Covid-19 tend to be milder in adolescents. Nevertheless, their perception, attitude, and behavior towards Covid-19 deserve attention since they would also contribute to the success of Covid-19 control. Therefore, the aim of this study was to examine the perceived severity, susceptibility, attitudes, and behavior toward Covid-19 among high school students. This was a cross-sectional study conducted in five schools in Surabaya and Sidoarjo. Questionnaires were given online to teachers who then forwarded them to high school students. Data were taken from July to October 2021. Attitude and behavior were examined using the scoring previously tested. The data were then analyzed using Mann-Whitney U and Spearman's correlation tests. The significance level was set at p<0.05. More than 50% of students had good preventive behavior, the most frequent one was wearing masks (87.3%), followed by washing hands (73%). The behavior was correlated with their attitude (r= 0.285, p=0.000). Fifty-three percent of the respondents felt they would experience mild symptoms if they were infected with Covid-19. Most students perceived that they were susceptible to getting infected with Covid-19. Significant results were obtained using the Mann-Whitney test on gender toward attitudes and behavior (p<0.05). There were significant correlations between the mother's educational level (r=0.164, p=0.001) and the father's educational levels (r=0.120, p=0.013) with attitude toward Covid-19 control policies. Female students in Surabaya and Sidoarjo have better behavior in dealing with the Covid-19 pandemic. Parents' educational level plays a role in influencing the student's attitude toward Covid-19 control.